1998
DOI: 10.1037/0735-7044.112.1.126
|View full text |Cite
|
Sign up to set email alerts
|

A sensory-enhanced context facilitates learning and multiple measures of unconditioned stimulus processing in the preweanling rat.

Abstract: This study tested the hypothesis that increased processing or efficacy of the unconditioned stimulus (US) contributes to the facilitation of trace conditioning that occurs when preweanling rats are conditioned in a novel sensory-rich context. Experiment 1 extended previous findings (D. L. McKinzie & N. E. Spear, 1995) of facilitated acoustic trace conditioning in the 17-day-old rat in a sensory-enhanced versus a home odor context. In the enhanced or more familiar context, Experiment 2 tested rats of this age f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 57 publications
5
43
2
Order By: Relevance
“…However, Spear and his colleagues have proposed a hypothesis that may help to understand this effect (McKinzie and Spear 1995;Spear 1998, 2004). These authors observed that during conditioning, preweanling rats showed an increase in the orientation response to the CS (Kraebel et al 1998) and enhanced responses to the US (Brasser and Spear 1998) when trained in a sensory-enriched context and when the CS and US were contiguous. According to these authors, these changes may favor (particularly during infancy) processing of the events that constitute the conditioning episode, thereby facilitating learning (Brasser and Spear 1998;Kraebel et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Spear and his colleagues have proposed a hypothesis that may help to understand this effect (McKinzie and Spear 1995;Spear 1998, 2004). These authors observed that during conditioning, preweanling rats showed an increase in the orientation response to the CS (Kraebel et al 1998) and enhanced responses to the US (Brasser and Spear 1998) when trained in a sensory-enriched context and when the CS and US were contiguous. According to these authors, these changes may favor (particularly during infancy) processing of the events that constitute the conditioning episode, thereby facilitating learning (Brasser and Spear 1998;Kraebel et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These authors observed that during conditioning, preweanling rats showed an increase in the orientation response to the CS (Kraebel et al 1998) and enhanced responses to the US (Brasser and Spear 1998) when trained in a sensory-enriched context and when the CS and US were contiguous. According to these authors, these changes may favor (particularly during infancy) processing of the events that constitute the conditioning episode, thereby facilitating learning (Brasser and Spear 1998;Kraebel et al 1998). Given that Spear and his collaborators limited their studies to the acquisition phase of conditioning, it would be interesting to extend these observations to extinction training, in order to explore whether the salience of the context also affects processing of the CS during extinction in preweanling rats.…”
Section: Discussionmentioning
confidence: 99%
“…It should not be a surprise that infant rats --in some cases--show more contextual fear conditioning than adults, given other instances in which infants have seemed more sensitive to context than older animals: CS conditioning is disrupted by a change in olfactory context more extremely for infants than adults (Solheim, Hensler, & Spear, 1980); Pavlovian trace conditioning is regularly facilitated in infant rats by a salient olfactory and visual context but unaffected by the same manipulations in adults (Brasser & Spear, 1998;McKinzie & Spear, 1995); the presence of a familiar context such as odor of the rat's home is more likely to affect infant learning than adult learning (Spear, Kucharski, & Hoffmann, 1985); and infants are more likely than older animals to show enhanced unconditioned responding to visual, auditory and tactile stimuli in the presence of a context rich in novel odor (Brasser & Spear, 1998;Kraebel, Vizvary, & Spear, 1998).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…In these cases, infants have seemed equally or more effective in contextual fear conditioning than older animals, including adults (e.g., Brasser & Spear, 2004;Carew & Rudy, 1991;Lariviere et al, 1990). And when a discrete auditory CS predicts the footshock within a salient olfactory context, contextual fear conditioning in the infant exceeds that in the adult, even when conditioning to the CS is held constant (Brasser & Spear, 2004;Mckinzie & Spear, 1995).It should not be a surprise that infant rats --in some cases--show more contextual fear conditioning than adults, given other instances in which infants have seemed more sensitive to context than older animals: CS conditioning is disrupted by a change in olfactory context more extremely for infants than adults (Solheim, Hensler, & Spear, 1980); Pavlovian trace conditioning is regularly facilitated in infant rats by a salient olfactory and visual context but unaffected by the same manipulations in adults (Brasser & Spear, 1998;McKinzie & Spear, 1995); the presence of a familiar context such as odor of the rat's home is more likely to affect infant learning than adult learning (Spear, Kucharski, & Hoffmann, 1985); and infants are more likely than older animals to show enhanced unconditioned responding to visual, auditory and tactile stimuli in the presence of a context rich in novel odor (Brasser & Spear, 1998;Kraebel, Vizvary, & Spear, 1998).Thus, the goal of the present series of experiments was to examine fear conditioning to an olfactory context, the type of situation where infant rats seem to show the strongest disposition for contextual conditioning. They were intended to replicate and extend previous experiments (viz., Brasser & Spear, 2004) suggesting that contextual fear conditioning in infants may exceed that of adults, particularly when an auditory CS within an olfactory context also predicts the US.…”
mentioning
confidence: 99%
“…Rat pups as young as PD 17 can express conditioned fear after explicit-cue fear conditioning (Rudy 1992(Rudy , 1993Stanton 2000;Barnet and Hunt 2005), indicating that the amygdala and output systems are intact. Although PD 17 rats have demonstrated conditioning to an enhanced context (Brasser and Spear 1998), most studies demonstrate that rats younger than PD 23 cannot demonstrate long-term memory for contextual fear conditioning (Rudy 1993(Rudy , 1994Stanton 2000;Raineki et al 2009), which has been interpreted as a delay in the emergence of hippocampus function. This is curious given that rat pups younger than PD 23 can complete many hippocampusdependent tasks (see Stanton 2000), express a fearful response, and show context-dependent effects, such as latent inhibition and renewal following extinction Richardson 2005, 2007).…”
mentioning
confidence: 99%